Harmonization of Prophetic Dimensions and Locality in Bawor Characters - Cahya Ningsih, Ade (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
This study aims to describe the prophetic dimension and locality in the famous Bawor figure in Banyumas society. This research uses qualitative research methods that are descriptive. Data collection techniques using documentation. At the data analysis stage using Charles Sanders Peirce's semiotic analysis with three main elements, namely icons, indexes, and symbols. The results of the data describe that there is a harmony of prophetic dimensions and locality reflected in the figure of Bawor. This harmony is reflected in three important elements relevant to Kuntowijoyo's thought, namely humanization, liberation, and transcendental. The element of humanization is cablaka and represents the culture of the equality Banyumas people. The element of liberation is reflected in the character of Bawor who has a prevent the misfortune and always helps others in kindness. And the transcendental element connects that all the characters possessed by Bawor are based on Islamic values.